(3GdMeGjI GdLfGFjI ddYbGQ (B/ s - (3eUWai CMeO YHOGdYGd CMeO GdSHGYis; (3YeQ eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3JYGXeJ bjeI GdYbGQ ai GdBhfI GdCNjQI(B: (3ShGA GdeSchf efg Ch ZjQg(B: (3h gh eG COi Edi JYGXe GdUQGY Ydi GdESJFKGQ Hg edckG h MjGRkI(B: (3h JQGab eY Pdc GdQZHI ZjQ GdeTQhYI ai GdGSJFKGQ Hg Ydi NdGa GdbGfhf(B: (3Ch MJi GJNGP GdJUQa ZjQ GdeTQhY ajg hSjdI dSdH eGd GdZjQ(B: (3h COQc GdeTQY Pdc eHcQkG aSf ef GdbhGfjf eG jcad MeGjI GdYbGQ(B: (3h eY Pdc aEf GdJWHjb GdYedi dJdc GdbhGfjf CXgQ GdMGLI deRjO ef GdJTQjYGJ GdJi Jcad Jdc GdMeGjI HTbjgG GdehVhYi h GdELQGFi(B: (3h dG SjeG MeGjI GdMjGRI GdaYdjI ddYbGQ MjK jeKd GdYGed GdRefi YfUQkG aYGdkG ai JMbjb Jdc GdMeGjI h gh eG jbJVi eRjOkG ef GdVHW HeG jcad GdJfajP GdaYGd ddbhGfjf h GdbQGQGJ PGJ GdUdI(B: (3h de Jcf edcjI GdYbGQ ChaQ MXkG ef MjGRJg(B: (3ade jNJU GdeTQY edcjI GdYbGQ HfUhU Jcad MeGjJgG(B: (3HGSJKfGA eGhQO HNUhU JLQje GdJUQa ai GdYbGQ ef ZjQ UGMH GdMb ai GdJUQa ajg h Pdc ai SjGb JLQje GdfUH(B: (3ef Ke abO HOJ GdMGLI dEfTGA eMceI YbGQjI eJNUUI(B: (3JNJU HGdYbGQ Ohf ShGg(B: (3ljTQlY dgG ef GdfUhU GdehVhYjI h GdELQGFjI eG jcad MeGjI GdYbGQ ShGA ai MjGRJg Ch edcjJgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2018s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B375-412s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdMeGjI GdLfGFjI s; (3GdYbGQGJ s; (3edcjI GdYbGQ s; (3GdfUH hGdGMJjGds; (3GdTgQ GdYbGQis; (3GdMeGjI GdGLQGFjIs; (3GdeScf hedMbGJgs; (3GdSajfI GdeSchfIs; (3GdJYOi Ydi YbGQGJ GdOhdIs; (3efGRYGJ GdMjGRIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs